What Does the Circular Household of the Future Look Like? An Expert-Based Exploration - Saskia Keesstra; Tamara Metze; Linda Ofori; Marleen Buizer; Saskia Visser (Land, 2022)
Circularity is a necessity for the future of our society but individual households often find it difficult to contribute to this transition. This paper presents possible future visions of circular (and climate-neutral) households, inside and outside the house, regarding their contributions to the circular society, and taking into account food, energy, waste, household devices, and recreation. We combined expert interviews and a literature review to (1) explore imaginable futures for circular households, and (2) make a qualitative evaluation of the inside- and outside-house influences of households on a climate-neutral and circular society. Interviewees were selected to represent different scientific backgrounds. The four household types were organized according to more local or global, and collective or individual, levels: (1) the Househood (centering around neighborhoods); (2) the HouseNet (connecting households); (3) the Sharing Household (sharing goods between households); and (4) the Designing Household (input from circular-by-design products). The analysis shows that households can become more circular by connecting developments in social, ecological, and technological systems, such as those in price dynamics, policies, or land-use design. However, barriers and limitations need attention, including: (1) public awareness and willingness to change; (2) economic models; (3) waste; and (4) social justice.